Impact of sleep quality on academic achievements of undergraduate medical students: a cross-sectional study from Saudi Arabia - Arwa Khaled; Dalia Almaghaslah; Ayesha Siddiqua; Geetha Kandasamy; Khalid Orayj (BMC Medical Education)
Abstract Background Sleep is an active process that affects human health and quality of life. Sleep is essential for learning and memory consolidation. Good sleep is required for good academic performance. Sleep disorders are common among medical students, due to the high academic load, stressful life, and hectic schedule. Therefore, this study aims to assess sleep quality among medical students. Methods A cross-sectional study was conducted among medical students at King Khalid University by using the Pittsburgh sleep quality index (PSQI) to assess sleep duration, sleep efficiency, sleep latency, and global PSQI score. Participants were enrolled from second to sixth year. Bivariate and multivariate logistic regression were used to predict factors related to poor sleep quality. Results Out of 514 medical students, 453 (88.1%) of students exhibited poor sleep quality. Fourth year students were less likely to have poor sleep quality (AOR, 0.381; CI, 0.158–0.934) p = 0.035 and students with regular sleep schedule were more likely to be good sleepers (AOR,0.349; CI, 0.129–0.940) p = 0.037. Additionally, students who had more than five courses per semester more frequently had daytime sleepiness p = 0.03. However, Insufficient sleep was not significantly affected by factors like gender, different age groups, number of courses per semester, daytime sleeping, and students with varying Grade Point Averages (GPA). Conclusion Poor sleep quality is common among medical students, which may affect academic performance and general health. It is essential to educate them about good sleep hygiene and time management skills.